Locating control points in aerial images with a multi-scale approach based on terrestrial image patches - Berveglieri, Adilson [UNESP]; Tommaselli, Antonio Maria Garcia [UNESP] (Wiley-Blackwell, 2015)
The objective of the proposed approach is to locate and measure ground control points in aerial images when large image search spaces are defined due to the use of inaccurate initial exterior orientation parameters, such as those provided by consumer-grade navigation systems. Vertical terrestrial image patches covering control point areas are generated and compared with aerial patches using feature- and area-based matching algorithms to automatically determine their corresponding positions in aerial images with sub-pixel precision. The approach is based on techniques for both image search space reduction and adaptive least squares matching. Experiments with real data were performed with bundle block triangulation and the results were analysed using control and check points in both object and image spaces. The proposed technique enabled a significant reduction in the search space within which it was feasible to successfully locate control points. Compared with manual measurements, the results obtained by the automatic technique were more accurate, achieving one-fifth of the ground sample distance in planimetric check point discrepancies.ResumeL'objectif de l'approche proposee est de localiser des points d'appui dans des images aeriennes lorsque l'espace de recherche est tres grand en raison de parametres d'orientation externe initiaux peu precis, comme ceux fournis par des systemes de navigation du commerce. Des imagettes verticales terrestres des points d'appui sont comparees avec des fenetres d'images aeriennes au moyen d'algorithmes d'appariement bases sur les surfaces ou sur les primitives pour la determination automatique de leurs positions avec une precision sub-pixel. Cette approche est basee sur des techniques de reduction de l'espace de recherche et d'ajustement adaptatif par moindres carres. Des experiences ont ete realisees sur des donnees reelles avec une compensation par faisceaux, et les resultats ont ete analyses avec des points d'appui et des points de controle, tant dans l'espace objet que dans l'espace image. La technique proposee a permis une reduction significative de l'espace de recherche dans lequel il etait possible de localiser les points d'appui avec succes. Les resultats obtenus par cette technique ont conduit a des resultats plus precis que par des mesures manuelles, avec des ecarts d'un cinquieme de pixel sur les coordonnees planimetriques des points de controle.ZusammenfassungDas Ziel dieses Ansatzes ist es, Passpunkte in Luftbildern zu lokalisieren und zu messen, wenn der Suchraum durch ungenaue Naherungen fur die Parameter der au ss eren Orientierung, wie sie durch einfache Navigationssysteme geliefert werden, sehr gro ss ist. Es werden, mit Blickrichtung auf den Boden, terrestrisch Bildausschnitte erfasst, die die Passpunktbereiche abdecken. Diese Bildausschnitte werden mit Luftbildausschnitten mittels merkmalsbasierter und intensitatsbasierter Bildzuordnung verglichen, um die Positionen im Luftbild mit Subpixel-Genauigkeit zu ermitteln. Fur dieses Verfahren werden eine Suchraumreduzierung und eine adaptive Kleinste-Quadrate-Zuordnung eingesetzt. Es werden Experimente mit realen Daten und einer Bundelblockausgleichung durchgefuhrt, und die Ergebnisse mittels Pass- und Kontrollpunkten im Objekt- und im Bildbereich analysiert. Die vorgeschlagene Technik erlaubt eine signifikante Reduktion des Suchbereichs und trotzdem erfolgreicher Lokalisierung der Passpunkte. Im Vergleich zu manuellen Messungen war die Genauigkeit hoher und es wurde eine planimetrische Genauigkeit der Passpunkte von 1/5 der Bodenpixelgro ss e erreicht.ResumenEl objetivo de la metodologia propuesta es localizar y medir puntos de control en imagenes aereas cuando las areas de busqueda en dichas imagenes son grandes debido a la baja precision de las orientaciones exteriores iniciales, como las proporcionadas por sistemas de navegacion. Se generan imagenes verticales de referencia cubriendo los puntos de control a partir de imagenes verticales terrestres y se comparan con las imagenes aereas usando algoritmos de correspondencia de imagenes basados en area y caracteristicas para determinar automaticamente sus posiciones en las imagenes con precision sub-pixel. La metodologia se basa tanto en tecnicas de reduccion del espacio de busqueda como correspondencia de minimos cuadrados adaptativos. En las pruebas con datos reales se han realizado con ajuste de haces y los resultados se han analizado usando puntos de control y comprobacion tanto en el espacio imagen como en el espacio objeto. La metodologia propuesta permite una significante reduccion del espacio de busqueda donde localizar con exito los puntos de control. En comparacion con la medicion manual, los resultados son mas precisos alcanzando discrepancias planimetricas de un quinto del tamano del pixel en los puntos de comprobacion.?? ??????????????????,??????????,?????????????????????????????????????????????????????????????????,??????:??????????????????????????????????????????????,???????????????????????,??????????????,?????????????,????????????,?????????????????02??????
Keywords: Bundle block adjustment; Labelling of differences; LSM; Orientation; SIFT